2018
DOI: 10.1186/s40634-018-0134-8
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic analysis of the whole articular capsule of the shoulder joint, with reference to the capsular attachment and thickness

Abstract: BackgroundAlthough conventional Bankart repair has been the accepted procedure for traumatic anterior glenohumeral instability, the humeral avulsion of the glenohumeral ligament or an elongation of the capsule remains challenging to decide the appropriate treatment. The anatomical knowledge regarding the whole capsule of glenohumeral joint is necessary to accurately treat for the capsular disorders. The aims of the current study were to investigate the anatomical features of capsular attachment and thickness i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…In the study by Nimura et al, 20 it was stated that the superior capsule had an average width of attachment to the greater tuberosity of 4.4 to 9.1 mm, which is different from stating that the thickness of the superior capsule ranged from 4.4 to 9.1 mm throughout. Indeed, in the study conducted by Momma et al, 19 in a color representation through 3-dimensional micro-computed tomography images of the variations in capsular thickness distribution, it was shown that the superior parts of the capsule were consistently thinner, ranging from 0.1 to 0.5 mm, whereas at the glenoid and humeral attachment sites the superior, inferior and anterior parts of the capsule were thicker, ranging from 0.5 to 8.0 mm. The results of the present study suggest that the decreased superior translation of the humeral head shown in the biomechanical studies that used the SCR cadaveric models might have been explained by the influence of other external variables.…”
Section: Discussionmentioning
confidence: 94%
“…In the study by Nimura et al, 20 it was stated that the superior capsule had an average width of attachment to the greater tuberosity of 4.4 to 9.1 mm, which is different from stating that the thickness of the superior capsule ranged from 4.4 to 9.1 mm throughout. Indeed, in the study conducted by Momma et al, 19 in a color representation through 3-dimensional micro-computed tomography images of the variations in capsular thickness distribution, it was shown that the superior parts of the capsule were consistently thinner, ranging from 0.1 to 0.5 mm, whereas at the glenoid and humeral attachment sites the superior, inferior and anterior parts of the capsule were thicker, ranging from 0.5 to 8.0 mm. The results of the present study suggest that the decreased superior translation of the humeral head shown in the biomechanical studies that used the SCR cadaveric models might have been explained by the influence of other external variables.…”
Section: Discussionmentioning
confidence: 94%
“…Yellow arrows indicated the border of each partition. The SWE images were displayed in color-coded map with harder tissue represented in red and softer tissue in blue the anterior margin of the highest impression of the greater tuberosity [22][23][24][25]31]. Kato et al demonstrated that the ISP muscle was comprised of two parts, namely the transverse and oblique parts [15].…”
Section: Discussionmentioning
confidence: 99%
“…Recent detailed anatomical studies demonstrated that the ISP muscle was anatomically divided into two or three distinct neuromuscular partitions based on differences in their attachment sites, muscle fiber directions, and intramuscular innervations [3,6,15,22,31]. Several authors demonstrated that the anterior-most region of the humeral insertion of the ISP muscle almost reached the anterior margin of the highest impression of the greater tuberosity [22][23][24][25]31]. In addition, Kato et al found that one of the partitions of the ISP muscle was innervated by branches arising from the supraspinatus muscle [15].…”
Section: Introductionmentioning
confidence: 99%
“…Although the authors examined the length of the labral attachment using 2-hour clock-referent intervals, they did not provide the detailed values for the respective length at each clock position. Momma et al 15 reported that the length of the labral attachment viewed from a cross section of the glenoid neck was 7.4 mm at the posterior edge of the origin of the long head of the triceps brachii, which was slightly inferior to the 7 o'clock position, and the length was greater than at the 9 o'clock position. However, the position of the posterior edge of the origin of the long head of the triceps brachii was unclear.…”
Section: Discussionmentioning
confidence: 99%